Enabling Ideal Selective Solar Absorption with 2D Metallic Dielectric Photonic Crystals. (16th September 2014) - Chou, Jeffrey B.; Yeng, Yi Xiang; Lee, Yoonkyung E.; Lenert, Andrej; Rinnerbauer, Veronika; Celanovic, Ivan; Soljačić, Marin; Fang, Nicholas X.; Wang, Evelyn N.; Kim, Sang‐Gook
<x xml:space="preserve">Abstract</x> A metallic dielectric photonic crystal with solar broadband, omni‐directional, and tunable selective absorption with high temperature stable (1000 °C, 24 hrs) properties is fabricated on a 6" silicon wafer. The broadband absorption is due to a high density of optical cavity modes overlapped with an anti‐reflection coating. Results allow for large‐scale, low cost, and efficient solar‐thermal energy conversion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>